2015
DOI: 10.1123/jpah.2014-0126
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of the Link Between Parent and Child Physical Activity Levels: The Moderating Role of Parental Encouragement

Abstract: Background Research on adolescent physical activity is mixed regarding the role of parent activity. This study tested parent encouragement, direct modeling, and perceived influence as moderators of objectively-measured (accelerometer) parent and child moderate-to-vigorous physical activity (MVPA) associations. Methods Parent-child dyads (n = 423; Mchild age = 11.33 yrs.) wore accelerometers for 7 days; parents completed surveys. Hierarchical linear regression models tested moderation using a product of const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
6
32
0
1
Order By: Relevance
“…Research has also shown that family support can play an important role in the PA level of the adolescents [24,25,52] and, as our results show, the students with a lack of family support, parental connectivity and peer support have higher odds for being physically inactive in compared to students with such supports. Previous research has shown that increased parental encouragement is positively associated with increased physical activity levels in both genders [53].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Research has also shown that family support can play an important role in the PA level of the adolescents [24,25,52] and, as our results show, the students with a lack of family support, parental connectivity and peer support have higher odds for being physically inactive in compared to students with such supports. Previous research has shown that increased parental encouragement is positively associated with increased physical activity levels in both genders [53].…”
Section: Discussionsupporting
confidence: 74%
“…Previous research has shown that increased parental encouragement is positively associated with increased physical activity levels in both genders [53]. By providing facilities in terms of equipment, physically active school transportation (walking/cycling) and planning for leisure time PA, such as playing soccer or other sports with their children, parents can have an active role in increasing PA levels [24,25,54]. Therefore, families or guardians should be taken into consideration when planning interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within paediatric obesity treatment, parent‐only treatment is recognized as being as effective as parent and child treatment . Parents facilitate, support, and influence their child's physical activity, and modelling exercise appears to have influence on child activity patterns . For clinicians working in family‐based weight management programs, expert and professional guidelines do not provide suggestions for family‐based approaches to physical activity, aside from a few examples of activities families could do together.…”
Section: Discussionmentioning
confidence: 99%
“…Parents play an important role in shaping children's health behaviours and may do so through direct modelling (i.e. engaging in LTPA behaviours observed by children -"do together"), which increases the likelihood that children will emulate their parents' actions [20,48,53,54]. Parents are the primary inhibitors of their children's participation in LTPA [6], and they have a variety of direct and indirect ways of reinforcing children's LTPA [8].…”
Section: Discussionmentioning
confidence: 99%